Host identity shapes Endozoicomonas composition in coral microbiomes across depths and marine protected areas at Little Cayman Island - Madelaine L. Brown; Andrew J. Maritan; Gretchen Goodbody-Gringley; Matthew L. Doherty; Alex D. Chequer; Frank J. Stewart; Zoe A. Pratte (Coral Reefs, 2026)
The bacterial genus Endozoicomonas is prevalent and abundant in the microbiome of many corals, but the combination of environmental and host factors shaping its distribution remains uncertain. In this study, we used 16S rRNA gene sequencing to examine the distribution of Endozoicomonas across hard ( Porites astreoides , Montastraea cavernosa , Agaricia spp.) and soft coral ( Muricea spp., Gorgoniidae, Cladiellidae, Malacalcyonacea) microbiomes across a depth gradient from shallow (4.5 m) to upper mesophotic zones (36.6 m) at four sites around the Little Cayman Island, including two marine protected areas. Endozoicomonas was abundant across all coral microbiomes, with soft corals exhibiting near-total dominance (relative abundance range 0.1–99%, median 55.3%) by this genus and notable abundances (range 0–96%, median 22.2%) in hard corals. Endozoicomonas composition was strongly structured by coral host identity across sites and depths, with each coral type harboring two to four unique Endozoicomonas amplicon sequence variants. Site and depth also contributed to Endozoicomonas abundance in soft and hard corals, respectively, where relative abundances were highest at unprotected sites in soft corals and in shallow to mid photic zones in hard corals. These findings suggest that Endozoicomonas abundance is shaped by both coral host identity and local environmental conditions.

Fate tracking of Acropora cervicornis colonies post-outplanting reveals genotype-specific responses to marine heatwaves - Gretchen Goodbody-Gringley; Brett D. Jameson; Haley A. Davis; Janna L. Randle; Matthew L. Doherty; Jack V. Johnson; Alex D. Chequer; John F. Bruno (Coral Reefs, 2026)

Life cycle assessment of recyclable all-carbon thin-film transistors for LCD displays: toward sustainable nano-enabled electronics - G. Melike Urper-Bayram; James L. Doherty; Arianna Livieri; Nathan Bossa; D. Hristozov; Aaron D. Franklin; R. Mark Wiesner (Clean Technologies and Environmental Policy, 2026)

Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

Spatial footprint of maritime vessels in the waters of a fast-growing coastal megalopolis - Stephen D.J. Lang; Philip D. Doherty; Brendan J. Godley; Shing Yip Lee; Felix Leung; Manmohan D. Sharma; Kristian Metcalfe (Marine Policy, 2025)

P24-02 The EIRE Research Project: Exposure to Neonicotinoid Insecticides in Ireland and their Cellular Toxicity In vitro - D.M. Doherty; S.A. Wrobel; H.U. Käfferlein; H.M. Koch; D. Bury; C. Slattery; S. Lee; A. Connolly (Toxicology Letters, 2025)

Effects of illumination and pot design on catch and bycatch when targeting northern shrimp (Pandalus borealis) using white LED PotLights - Thomas W. Horton; Robert Enever; Brendan J. Godley; Pete Kibel; Donald Malone; Duncan McAndrew; Philip D. Doherty (Ocean & Coastal Management, 2025)

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Ten questions concerning the future of residential indoor air quality and its environmental justice implications - D. Booker; G. Petrou; L. Chatzidiakou; D. Das; F. Farooq; L. Ferguson; OE.I. Jutila; K. Milczewska; M. Modlich; A. Moreno-Rangel; S.K. Thakrar; A.M. Yeoman; et al. (Building and Environment, 2025)

‘Megafire’—You May Not Like It, But You Cannot Avoid It - Grant D. Linley; Chris J. Jolly; Tim S. Doherty; William L. Geary; Dolors Armenteras; Claire M. Belcher; Rebecca Bliege Bird; Andrea Duane; Michael‐Shawn Fletcher; Melisa A. Giorgis; Angie Haslem; Gavin M. Jones; et al. (Global Ecology and Biogeography, 2025)
Aim The term ‘megafire’ is increasingly used to describe large fires worldwide. We proposed a size‐based definition of megafire—fires exceeding 10,000 ha arising from single or multiple related ignition events. A recent perspective in Global Ecology and Biogeography argues against a size‐based definition of megafire and suggest that the term is too emotive for scientific use. We highlight that many scientific terms originate from common terms. These terms are often defined once they enter the scientific lexicon, enhancing both scientific understanding and public communication. We argue that standardised definitions facilitate better prediction, preparation, and management of fire events. Location Worldwide. Time Period 2022–2023. Methods We conducted an updated structured review of the term ‘megafire’ and its use and definition in the peer‐reviewed scientific literature, collating definitions and descriptions and identifying the criteria frequently invoked to define the term. Results We demonstrate an increase in the use of ‘megafire’ in the scientific literature since our original definition in 2022, with many studies adopting the > 10,000 ha size‐based criterion. Main Conclusions We contend that abandoning the term is neither practical, possible, nor beneficial. Instead, consistent usage underpinned by clear definitions is essential. Adopting a clear, size‐based definition of megafire strengthens clarity and comparability across research and management practices globally. Precision in terminology is crucial for advancing research, improving communication, and informing effective fire management and policy.

Animal-borne sensors reveal high human impact on soundscapes near a critical sea turtle nesting beach - Francesco Garzon; Pierre Didier Agamboue; Jack A. Boyle; Philip D. Doherty; Angela Formia; Brendan J. Godley; Lucy A. Hawkes; David A. Mann; Sara M. Maxwell; Richard J. Parnell; Stephen K. Pikesley; Guy-Phillipe Sounguet; et al. (Biological Conservation, 2024)

Escaping the cohort of concern: in vitro experimental evidence supports non-mutagenicity of N-nitroso-hydrochlorothiazide - R. D. Gandhi; S. Hickert; Y. Hoevelmann; C. D. Mee; J. Schlingemann; A. Adams; A. Blanazs; S. Simon; J. Elloway; L. Rigger; A. Teasdale; C. V. Beaumont; et al. (Archives of Toxicology, 2024)

Phenotypic variability of Montastraea cavernosa and Porites astreoides along a depth gradient from shallow to mesophotic reefs in the Cayman Islands - Matthew L. Doherty; Alex D. Chequer; Tali Mass; Gretchen Goodbody-Gringley (Coral Reefs, 2024)
Phenotypic variability is the ability of the same species to express different phenotypes under different environmental conditions. Several coral species that exist along a broad depth distribution have been shown to differ in skeletal morphology and nutrient acquisition at different depths, which has been attributed to variability in response to differing levels of light availability. This study examined the phenotypic variability of two common depth generalist corals, Montastraea cavernosa and Porites astreoides, along a gradient from 10 to 50 m in the Cayman Islands, by examining changes in skeletal morphology, photophysiology, symbiont cell density, and chlorophyll concentration. Skeletal features of M. cavernosa were found to increase in size from 10 to 30 m, but returned to smaller sizes from 30 to 50 m, while P. astreoides skeletal features continued to increase in size from 10 to 40 m. No differences were observed in either symbiont density or chlorophyll concentration across depths for either species. However, all photophysiological parameters exhibited significant depth-dependent variations in both species, revealing adaptive strategies to different light environments. These results suggest that both species have high variability in response to depth. Patterns of skeletal morphology and photophysiology, however, suggest that M. cavernosa may be more variable in regulating photosynthetic efficiency compared to P. astreoides , which likely facilitates the broader depth distribution of this species.

Accuracy of patient race and ethnicity data in a central cancer registry - Rachel R. Codden; Carol Sweeney; Blessing S. Ofori-Atta; Kimberly A. Herget; Kacey Wigren; Sandra Edwards; Marjorie E. Carter; Rachel D. McCarty; Mia Hashibe; Jennifer A. Doherty; Morgan M. Millar (Cancer Causes & Control, 2024)

Vertical trophic structure and niche partitioning of gelatinous predators in a pelagic food web: Insights from stable isotopes of siphonophores - Elizabeth D. Hetherington; Hilary G. Close; Steven H. D. Haddock; Alejandro Damian‐Serrano; Casey W. Dunn; Natalie J. Wallsgrove; Shannon C. Doherty; C. Anela Choy (Limnology and Oceanography, 2024)
Gelatinous zooplankton are increasingly recognized as key components of pelagic ecosystems, and there have been many recent insights into their ecology and roles in food webs. To examine the trophic ecology of siphonophores (Cnidaria, Hydrozoa), we used bulk (carbon and nitrogen) and compound‐specific (nitrogen) isotope analysis of individual amino acids (CSIA‐AA). We collected samples of 15 siphonophore genera using blue‐water diving, midwater trawls, and remotely operated vehicles in the California Current Ecosystem, from 0 to 3000 m. We examined the basal resources supporting siphonophore nutrition by comparing their isotope values to those of contemporaneously collected sinking and suspended particles (0–500 m). Stable isotope values provided novel insights into siphonophore trophic ecology, indicating considerable niche overlap between calycophoran and physonect siphonophores. However, there were clear relationships between siphonophore trophic positions and phylogeny, and the highest siphonophore trophic positions were restricted to physonects. Bulk and source amino acid nitrogen isotope (δ 15 N) values of siphonophores and suspended particles all increased significantly with increasing collection depth. In contrast, siphonophore trophic positions did not increase with increasing collection depth. This suggests that microbially reworked, deep, suspended particles with higher δ 15 N values than surface particles, likely indirectly support deep‐pelagic siphonophores. Siphonophores feed upon a range of prey, from small crustaceans to fishes, and we show that their measured trophic positions reflect this trophic diversity, spanning 1.5 trophic levels (range 2.4–4.0). Further, we demonstrate that CSIA‐AA can elucidate the feeding ecology of gelatinous zooplankton and distinguish between nutritional resources across vertical habitats. These findings improve our understanding of the functional roles of gelatinous zooplankton and energy flow through pelagic food webs.

Ozone at Mace Head, Ireland from 1987 to 2021: Declining baselines, phase-out of European regional pollution, COVID-19 impacts - Richard G. Derwent; David D. Parrish; Alistair J. Manning; T. Gerard Spain; Peter G. Simmonds; Simon O'Doherty (Atmospheric Environment, 2024)

A nose for trouble: ecotoxicological implications for climate change and disease in Saiga antelope (S. t. tatarica) - S. T. Mullineaux; J. M. McKinley; N. J. Marks; R. Doherty; D. M. Scantlebury (Environmental Geochemistry and Health, 2024)
In recent decades, Saiga antelope ( Saiga t. tatarica ) mass die-offs have become more common. The mass die-off of 2015 in central Kazakhstan, recorded 140,000 individual deaths across multiple herds. Previously, research has shown atmospheric humidity, the bacterium Pasteurella multocida serotype B, and resultant haemorrhagic septicaemia, were the primary cause. However, other synergistic factors may have impacted this process. Here we use a multivariate compositional data analysis (CoDA) approach to assess what other factors may have been involved. We show a pollutant linkage mechanism where relative humidity and dewpoint temperature combine with environmental pollutants, potentially toxic elements (e.g., Hg, As), complex carbon compounds (e.g., Acetone, Toluene), and inorganic compounds (e.g., CHx, SO 2 ) which affected the Saiga during the calving season (start and peak) and at the onset of the mass die-off. We suggest a mechanism for this process. Upon arrival at their carving grounds, the Saiga experienced a sudden precipitation event, a spike in temperatures, and resultant high humidity occurs. The infectious bacterium P . multocida serotype B then spreads. Further, environmental pollutants contained within steppe soils are released to the air, forming localised smog events, these synergistically combine, and mass die-off occurs.

Rise and fall of an avian oasis: Tracking the impacts of land use change in a key coastal wetland in the world's largest megalopolis - Felix Leung; Philip D. Doherty; Mingfeng Liu; Kristian Metcalfe; Brendan Godley; Shing Yip Lee (Science of The Total Environment, 2024)

Using coral holes to explore the historical ecology of Guam’s coral reefs - Jonathan D. Cybulski; John M. Doherty; Carly LaRoche; Kelly Donovan Gutkowski; Zizhan Luo; Elizabeth J. Malloy; Laurel MacMillan; Laurie Raymundo; Kiho Kim (Coral Reefs, 2023)

The stage-specific toxicity of per- and polyfluoroalkyl substances (PFAS) in nematode Caenorhabditis elegans - Seth D. Currie; Joseph Patrick Doherty; Kathy S. Xue; Jia-Sheng Wang; Lili Tang (Environmental Pollution, 2023)

Warming and hypoxia reduce the performance and survival of northern bay scallops ( Argopecten irradians irradians ) amid a fishery collapse - Stephen J. Tomasetti; Brendan D. Hallinan; Stephen T. Tettelbach; Nils Volkenborn; Owen W. Doherty; Bassem Allam; Christopher J. Gobler (Global Change Biology, 2023)
Warming temperatures and diminishing dissolved oxygen (DO) concentrations are among the most pervasive drivers of global coastal change. While regions of the Northwest Atlantic Ocean are experiencing greater than average warming, the combined effects of thermal and hypoxic stress on marine life in this region are poorly understood. Populations of the northern bay scallop, Argopecten irradians irradians across the northeast United States have experienced severe declines in recent decades. This study used a combination of high‐resolution (~1 km) satellite‐based temperature records, long‐term temperature and DO records, field and laboratory experiments, and high‐frequency measures of scallop cardiac activity in an ecosystem setting to quantify decadal summer warming and assess the vulnerability of northern bay scallops to thermal and hypoxic stress across their geographic distribution. From 2003 to 2020, significant summer warming (up to ~0.2°C year −1 ) occurred across most of the bay scallop range. At a New York field site in 2020, all individuals perished during an 8‐day estuarine heatwave that coincided with severe diel‐cycling hypoxia. Yet at a Massachusetts site with comparable DO levels but lower daily mean temperatures, mortality was not observed. A 96‐h laboratory experiment recreating observed daily temperatures of 25 or 29°C, and normoxia or hypoxia (22.2% air saturation), revealed a 120‐fold increased likelihood of mortality in the 29°C‐hypoxic treatment compared with control conditions, with scallop clearance rates also reduced by 97%. Cardiac activity measurements during a field deployment indicated that low DO and elevated daily temperatures modulate oxygen consumption rates and likely impact aerobic scope. Collectively, these findings suggest that concomitant thermal and hypoxic stress can have detrimental effects on scallop physiology and survival and potentially disrupt entire fisheries. Recovery of hypoxic systems may benefit vulnerable fisheries under continued warming.

Opportunistic camera surveys provide insight into discrete foraging behaviours in nurse sharks (Ginglymostoma cirratum) - Kristian J. Parton; Philip D. Doherty; Mark Parrish; Philip Shearer; Keith Myrick; Oliver N. Shipley; Austin J. Gallagher (Environmental Biology of Fishes, 2023)

What do you mean, ‘megafire’? - Grant D. Linley; Chris J. Jolly; Tim S. Doherty; William L. Geary; Dolors Armenteras; Claire M. Belcher; Rebecca Bliege Bird; Andrea Duane; Michael‐Shawn Fletcher; Melisa A. Giorgis; Angie Haslem; Gavin M. Jones; et al. (Global Ecology and Biogeography, 2022)
Background ‘Megafire’ is an emerging concept commonly used to describe fires that are extreme in terms of size, behaviour, and/or impacts, but the term’s meaning remains ambiguous. Approach We sought to resolve ambiguity surrounding the meaning of ‘megafire’ by conducting a structured review of the use and definition of the term in several languages in the peer‐reviewed scientific literature. We collated definitions and descriptions of megafire and identified criteria frequently invoked to define megafire. We recorded the size and location of megafires and mapped them to reveal global variation in the size of fires described as megafires. Results We identified 109 studies that define the term ‘megafire’ or identify a megafire, with the term first appearing in the peer‐reviewed literature in 2005. Seventy‐one (~65%) of these studies attempted to describe or define the term. There was considerable variability in the criteria used to define megafire, although definitions of megafire based on fire size were most common. Megafire size thresholds varied geographically from > 100–100,000 ha, with fires > 10,000 ha the most common size threshold (41%, 18/44 studies). Definitions of megafire were most common from studies led by authors from North America (52%, 37/71). We recorded 137 instances from 84 studies where fires were reported as megafires, the vast majority (94%, 129/137) of which exceed 10,000 ha in size. Megafires occurred in a range of biomes, but were most frequently described in forested biomes (112/137, 82%), and usually described single ignition fires (59% 81/137). Conclusion As Earth’s climate and ecosystems change, it is important that scientists can communicate trends in the occurrence of larger and more extreme fires with clarity. To overcome ambiguity, we suggest a definition of megafire as fires > 10,000 ha arising from single or multiple related ignition events. We introduce two additional terms – gigafire (> 100,000 ha) and terafire (> 1,000,000 ha) – for fires of an even larger scale than megafires.

Microbiome assembly in thawing permafrost and its feedbacks to climate - Jessica G. Ernakovich; Robyn A. Barbato; Virginia I. Rich; Christina Schädel; Rebecca E. Hewitt; Stacey J. Doherty; Emily D. Whalen; Benjamin W. Abbott; Jiri Barta; Christina Biasi; Chris L. Chabot; Jenni Hultman; et al. (Global Change Biology, 2022)
The physical and chemical changes that accompany permafrost thaw directly influence the microbial communities that mediate the decomposition of formerly frozen organic matter, leading to uncertainty in permafrost–climate feedbacks. Although changes to microbial metabolism and community structure are documented following thaw, the generality of post‐thaw assembly patterns across permafrost soils of the world remains uncertain, limiting our ability to predict biogeochemistry and microbial community responses to climate change. Based on our review of the Arctic microbiome, permafrost microbiology, and community ecology, we propose that Assembly Theory provides a framework to better understand thaw‐mediated microbiome changes and the implications for community function and climate feedbacks. This framework posits that the prevalence of deterministic or stochastic processes indicates whether the community is well‐suited to thrive in changing environmental conditions. We predict that on a short timescale and following high‐disturbance thaw (e.g., thermokarst), stochasticity dominates post‐thaw microbiome assembly, suggesting that functional predictions will be aided by detailed information about the microbiome. At a longer timescale and lower‐intensity disturbance (e.g., active layer deepening), deterministic processes likely dominate, making environmental parameters sufficient for predicting function. We propose that the contribution of stochastic and deterministic processes to post‐thaw microbiome assembly depends on the characteristics of the thaw disturbance, as well as characteristics of the microbial community, such as the ecological and phylogenetic breadth of functional guilds, their functional redundancy, and biotic interactions. These propagate across space and time, potentially providing a means for predicting the microbial forcing of greenhouse gas feedbacks to global climate change.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Exploring relationships between oxygen consumption and biologger‐derived estimates of heart rate in two warmwater piscivores - Claire L.J. Doherty; Aaron T. Fisk; Steven J. Cooke; Trevor E. Pitcher; Graham D. Raby (Journal of Fish Biology, 2022)
Estimating metabolic rate in wild, free‐swimming fish is inherently challenging. Here, we explored using surgically implanted heart rate biologgers to estimate metabolic rate in two warmwater piscivores, bowfin Amia calva (Linneaus 1766) and largemouth bass Micropterus salmoides (Lacepède 1802). Fish were surgically implanted with heart rate loggers, allowed to recover for 24 h, exposed to a netting and air exposure challenge, and then placed into respirometry chambers so that oxygen consumption rate ( Ṁ O2 ) could be measured in parallel to heart rate ( f H ) for a minimum of 20 h ( ca . 20 estimates of Ṁ O2 ). Heart rate across the duration of the experiment (at 19°C) was significantly higher in largemouth bass (mean ± s.d. , 45 ± 14 beats min −1 , range 18–86) than in bowfin (27 ± 9 bpm, range 16–98). Standard metabolic rate was also higher in largemouth bass (1.06 ± 0.19 mg O 2 kg −1 min −1 , range 0.46–1.36) than in bowfin (0.89 ± 0.17 mg O 2 kg −1 min −1 , range 0.61–1.28). There were weak relationships between f H and Ṁ O2 , with heart rate predicting 28% of the variation in oxygen consumption in bowfin and 23% in largemouth bass. The shape of the relationship differed somewhat between the two species, which is perhaps unsurprising given their profound differences in physiology and life history, illustrating the need to carry out species‐specific validations. Both species showed some potential for a role of f H in efforts to estimate field metabolic rates, although further validation experiments with a wider range of conditions ( e.g ., digestive states, swimming activity) would likely help improve the strength of the Ṁ O2 – f H relationship for use in field applications.

Threats of illegal, unregulated, and unreported fishing to biodiversity and food security in the Republic of the Congo - Philip D. Doherty; Benoit C. Atsango; Gaston Ngassiki; Appolinaire Ngouembe; Nathalie Bréheret; Eva Chauvet; Brendan J. Godley; Lucie Machin; Baudelaire Dissondet Moundzoho; Richard J. Parnell; Kristian Metcalfe (Conservation Biology, 2021)
Illegal, unregulated, and unreported (IUU) fishing poses a major threat to effective management of marine resources, affecting biodiversity and communities dependent on these coastal resources. Spatiotemporal patterns of industrial fisheries in developing countries are often poorly understood, and global efforts to describe spatial patterns of fishing vessel activity are currently based on automatic identification system (AIS) data. However, AIS is often not a legal requirement on fishing vessels, likely resulting in underestimates of the scale and distribution of legal and illegal fishing activity, which could have significant ramifications for targeted enforcement efforts and the management of fisheries resources. To help address this knowledge gap, we analyzed 3 years of vessel monitoring system (VMS) data in partnership with the national fisheries department in the Republic of the Congo to describe the behavior of national and distant‐water industrial fleets operating in these waters. We found that the spatial footprint of the industrial fisheries fleet encompassed over one‐quarter of the Exclusive Economic Zone. On average, 73% of fishing activity took place on the continental shelf (waters shallower than 200 m). Our findings highlight that VMS is not acting as a deterrent or being effectively used as a proactive management tool. As much as 33% (13% on average) of fishing effort occurred in prohibited areas set aside to protect biodiversity, including artisanal fisheries resources, and the distant‐water fleet responsible for as much as 84% of this illegal activity. Given the growth in industrial and distant‐water fleets across the region, as well as low levels of management and enforcement, these findings highlight that there is an urgent need for the global community to help strengthen regional and national capacity to analyze national scale data sets if efforts to combat IUU fishing are to be effective.

Spatial Ecology of Sub-Adult Green Turtles in Coastal Waters of the Turks and Caicos Islands: Implications for Conservation Management - Philip D. Doherty; Annette Cameron Broderick; Brendan John Godley; K. A. Hart; Q. Phillips; A. Sanghera; Thomas B. Stringell; J. T. Walker; Peter Bradley Richardson (Frontiers in Marine Science, 2020)

Assessing the Effects of Banana Pingers as a Bycatch Mitigation Device for Harbour Porpoises (Phocoena phocoena) - Lucy C. M. Omeyer; Philip D. Doherty; Sarah Dolman; Robert Enever; Allan Reese; Nicholas Tregenza; Ruth Williams; Brendan J. Godley (Frontiers in Marine Science, 2020)

Application of lipidomics in bivalve aquaculture, a review - Vincenzo A. Laudicella; Phillip D. Whitfield; Stefano Carboni; Mary K. Doherty; Adam D. Hughes (Reviews in Aquaculture, 2020)
Bivalve production is a relevant aquaculture activity in Europe; however, it is not developing with same extents of other aquaculture sectors due to causes connected with regulation stringency, labour cost, space availability, habitat loss as well as variability in recruitment events, climate change and diseases. Understanding the physiology and nutritional requirements of bivalves during aquaculture activities might result beneficial to fuel up the development of the sector. Lipids are important molecules as they are relevant components of cellular membranes acting in several physiological processes like reproduction, growth, immunological responses and energy reserve. Nevertheless, lipid diversity is still poorly understood despite the research efforts of the last decades. Technological advancements provide tools to unveil such diversity. Lipidomics, a branch of metabolomics, is the science targeting the lipidome (e.g. the totality of biological lipids in an organism). In this review, lipidomics, and its related concepts, are discussed providing an overview of recent lipidomics studies on bivalves. Lipidomics could result in several advantages if compared with traditional lipid profiling techniques; however, aims and scopes of future lipidomics studies should be expanded. Here, possible future applications of lipidomics in the context of bivalve production are presented and discussed. Unveiling the lipidome of marine bivalves could aid disclosing important information regarding nutrition, biology, physiology and epidemiology on bivalves. This knowledge, once applied, has the potential to improve bivalve production and the resilience of the sector to environmental changes.

Using Cumulative Impact Mapping to Prioritize Marine Conservation Efforts in Equatorial Guinea - Brittany T. Trew; Hedley S. Grantham; Christian Barrientos; Tim Collins; Philip D. Doherty; Angela Formia; Brendan J. Godley; Sara M. Maxwell; Richard J. Parnell; Stephen K. Pikesley; Dominic Tilley; Matthew J. Witt; et al. (Frontiers in Marine Science, 2019)

Seasonal changes in basking shark vertical space use in the north-east Atlantic - P. D. Doherty; J. M. Baxter; B. J. Godley; R. T. Graham; G. Hall; J. Hall; L. A. Hawkes; S. M. Henderson; L. Johnson; C. Speedie; M. J. Witt (Marine Biology, 2019)
Mobile marine species can exhibit vast movements both horizontally and vertically. Spatial analysis of vertical movements may help improve an understanding of the processes that influence space use. Previously, vertical space use of basking sharks ( Cetorhinus maximus ) in the north-east Atlantic described movements largely within waters of the continental shelf during summer and autumn months, with few records of detailed vertical behaviour during winter. We use archival satellite telemetry data from 32 basking sharks (12 females, 6 males, and 14 of unknown sex measuring 4–5 m ( n = 6), 5–6 m ( n = 10), 6–7 m ( n = 7), 7–8 m ( n = 8), and 8–9 m ( n = 1) estimated total length) tracked over 4 years (2012–2015). The satellite tags provided depth and temperature data for a cumulative 4489 days (mean 140 ± 97 days per shark, range 10–292 days) to describe vertical space use and thermal range of basking sharks in the north-east Atlantic. Basking sharks exhibit seasonality in vertical space use, revealing repeated ‘yo-yo’ movement behaviour with periods of occupancy at depths greater than 1000 m in late winter/early spring. Describing seasonal vertical space use in marine megavertebrates can increase knowledge of movements throughout their environment including physiological and morphological constraints to movement, nutrient transfer, and overlap with anthropogenic threats to inform future conservation strategies.

Insolation and disturbance history drive biocrust biodiversity in Western Montana rangelands - Rebecca A. Durham; Kyle D. Doherty; Anita J. Antoninka; Philip W. Ramsey; Matthew A. Bowker (Plant and Soil, 2018)

Biocrust moss populations differ in growth rates, stress response, and microbial associates - Kyle D. Doherty; Matthew A. Bowker; Anita J. Antoninka; Nancy C. Johnson; Troy E. Wood (Plant and Soil, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Resolving neutral and deterministic contributions to genomic structure in Syntrichia ruralis (Bryophyta, Pottiaceae) informs propagule sourcing for dryland restoration - Rob Massatti; Kyle D. Doherty; Troy E. Wood (Conservation Genetics, 2018)

Informing Marine Protected Area Designation and Management for Nesting Olive Ridley Sea Turtles Using Satellite Tracking - Tiffany M. Dawson; Angela Formia; Pierre D. Agamboué; Georges M. Asseko; François Boussamba; Floriane Cardiec; Emmanuel Chartrain; Philip D. Doherty; J. Michael Fay; Brendan J. Godley; Francis Lambert; Brice D. Koumba Mabert; et al. (Frontiers in Marine Science, 2017)

GPS Amplitude Scintillations over Kampala, Uganda, During 2010–2011 - Andrew O. Akala; Raphael Idolor; Florence M. D’Ujanga; Patricia H. Doherty (Acta Geophysica, 2016)

Adaptation services and pathways for the management of temperate montane forests under transformational climate change - Matthew J. Colloff; Michael D. Doherty; Sandra Lavorel; Michael Dunlop; Russell M. Wise; Suzanne M. Prober (Climatic Change, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Attenuation of nicotine-taking and nicotine-seeking behavior by the mGlu2 receptor positive allosteric modulators AZD8418 and AZD8529 in rats - Xia Li; Manoranjan S. D’Souza; Ana M. Niño; James Doherty; Alan Cross; Athina Markou (Psychopharmacology, 2016)

Role of Emitter and Severity of Aggression Influence the Agonistic Vocalizations of Geoffroy’s Spider Monkeys (Ateles geoffroyi) - José D. Ordóñez-Gómez; Jacob C. Dunn; Víctor Arroyo-Rodríguez; María G. Méndez-Cárdenas; Alejandra Márquez-Arias; Ana M. Santillán-Doherty (International Journal of Primatology, 2015)

Ecological mechanisms underpinning climate adaptation services - Sandra Lavorel; Matthew J. Colloff; Sue Mcintyre; Michael D. Doherty; Helen T. Murphy; Daniel J. Metcalfe; Michael Dunlop; Richard J. Williams; Russell M. Wise; Kristen J. Williams (Global Change Biology, 2015)
Ecosystem services are typically valued for their immediate material or cultural benefits to human wellbeing, supported by regulating and supporting services. Under climate change, with more frequent stresses and novel shocks, 'climate adaptation services', are defined as the benefits to people from increased social ability to respond to change, provided by the capability of ecosystems to moderate and adapt to climate change and variability. They broaden the ecosystem services framework to assist decision makers in planning for an uncertain future with new choices and options. We present a generic framework for operationalising the adaptation services concept. Four steps guide the identification of intrinsic ecological mechanisms that facilitate the maintenance and emergence of ecosystem services during periods of change, and so materialise as adaptation services. We applied this framework for four contrasted Australian ecosystems. Comparative analyses enabled by the operational framework suggest that adaptation services that emerge during trajectories of ecological change are supported by common mechanisms: vegetation structural diversity, the role of keystone species or functional groups, response diversity and landscape connectivity, which underpin the persistence of function and the reassembly of ecological communities under severe climate change and variability. Such understanding should guide ecosystem management towards adaptation planning.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Decisional Support throughout the Cancer Journey for Older Women Diagnosed with Early Stage Breast Cancer: A Single Institutional Study - Roseanna Presutti; Laura D’Alimonte; Merrylee McGuffin; Hanbert Chen; Edward Chow; Jean-Philippe Pignol; Lisa Di Prospero; Mary Doherty; Alex Kiss; Jennifer Wong; Justin Lee; Stanley Liu; et al. (Journal of Cancer Education, 2014)

Spatial impact of projected changes in rainfall and temperature on wheat yields in Australia - A. Potgieter; H. Meinke; A. Doherty; V. O. Sadras; G. Hammer; S. Crimp; D. Rodriguez (Climatic Change, 2013)

Social vulnerability in the context of bushfire risk at the urban-bush interface in Sydney: a case study of the Blue Mountains and Ku-ring-gai local council areas - Daminda Solangaarachchi; Amy L. Griffin; Michael D. Doherty (Natural Hazards, 2012)

Delineation of the molecular mechanism for disulfide stress-induced aluminium toxicity - Ming J. Wu; Patricia A. Murphy; Patrick J. O’Doherty; Stephen Mieruszynski; Mark Jones; Cindy Kersaitis; Peter J. Rogers; Trevor D. Bailey; Vincent J. Higgins (BioMetals, 2012)

The origins of neuromuscular fatigue post-stroke - S. Knorr; T. D. Ivanova; T. J. Doherty; J. A. Campbell; S. J. Garland (Experimental Brain Research, 2011)

Chromosome 15q24-25.1 variants, diet, and lung cancer susceptibility in cigarette smokers - Lori C. Sakoda; Melissa M. Loomis; Jennifer A. Doherty; Marian L. Neuhouser; Matt J. Barnett; Mark D. Thornquist; Noel S. Weiss; Gary E. Goodman; Chu Chen (Cancer Causes & Control, 2011)

Cohorts and consortia conference: a summary report (Banff, Canada, June 17–19, 2009) - Paolo Boffetta; Graham A. Colditz; John D. Potter; Laurence Kolonel; Paula J. Robson; Reza Malekzadeh; Daniela Seminara; Ellen L. Goode; Keun-Young Yoo; Paul Demers; Richard Gallagher; Ross Prentice; et al. (Cancer Causes & Control, 2011)

Pressure Filtration of Australian Bagasse Pulp - Thomas J. Rainey; William O. S. Doherty; D. Mark Martinez; Richard J. Brown; Neil A. Kelson (Transport in Porous Media, 2011)

Iron intake and markers of iron status and risk of Barrett’s esophagus and esophageal adenocarcinoma - Mark G. O’Doherty; Christian C. Abnet; Liam J. Murray; Jayne V. Woodside; Lesley A. Anderson; John D. Brockman; Marie M. Cantwell (Cancer Causes & Control, 2010)

Hypothesis testing of buoyant plume migration using a highly parameterized variable-density groundwater model at a site in Florida, USA - Alyssa M. Dausman; John Doherty; Christian D. Langevin; Joann Dixon (Hydrogeology Journal, 2010)

The Status of Coral Reefs in the Remote Region of Andavadoaka, Southwest Madagascar - M.O Nadon; D Griffiths; E Doherty; A Harris (Western Indian Ocean Journal of Marine Science, 2009)

Factors affecting Sciomyzidae (Diptera) across a transect at Skealoghan Turlough (Co. Mayo, Ireland) - Christopher D. Williams; James Moran; Owen Doherty; Rory J. Mc Donnell; Michael J. Gormally; Lloyd V. Knutson; Jean-Claude Vala (Aquatic Ecology, 2009)

Physical map of two tammar wallaby chromosomes: A strategy for mapping in non-model mammals - Janine E. Deakin; Edda Koina; Paul D. Waters; Ruth Doherty; Vidushi S. Patel; Margaret L. Delbridge; Bianca Dobson; James Fong; Yanqiu Hu; Cecilia van den Hurk; Andrew J. Pask; Geoff Shaw; et al. (Chromosome Research, 2008)

Long-term effects of hydropower installations and associated river regulation on River Shannon eel populations: mitigation and management - T. K. McCarthy; P. Frankiewicz; P. Cullen; M. Blaszkowski; W. O’Connor; D. Doherty (Hydrobiologia, 2008)

Radiative forcing from surface NO x emissions: spatial and seasonal variations - R. G. Derwent; D. S. Stevenson; R. M. Doherty; W. J. Collins; M. G. Sanderson; C. E. Johnson (Climatic Change, 2008)

Efficient and rapid Agrobacterium-mediated genetic transformation of durum wheat (Triticum turgidum L. var. durum) using additional virulence genes - Huixia Wu; Angela Doherty; Huw D. Jones (Transgenic Research, 2008)

Using movements and diet analyses to assess effects of introduced muskellunge (Esox masquinongy) on Atlantic salmon (Salmo salar) in the Saint John River, New Brunswick - R. Allen Curry; Chad A. Doherty; Timothy D. Jardine; Steven L. Currie (Environmental Biology of Fishes, 2007)

Turbulent mixing and mesoscale distributions of late‐stage fish larvae on the NW Shelf of Western Australia - M. G. MEEKAN; J. H. CARLETON; C. R. STEINBERG; A. D. MCKINNON; R. BRINKMAN; P. J. DOHERTY; A. HALFORD; S. DUGGAN; L. MASON (Fisheries Oceanography, 2006)
Light traps were deployed to describe vertical and cross‐shelf distributions of late‐stage larval fishes during five cruises in each of the 1997/98 and 1998/99 summers in the region of the Gulf of Exmouth on the southern North West Shelf of Western Australia. At each light trap station on a cross‐shelf transect we measured water temperature, salinity and chlorophyll a and used vertical plankton tows to estimate zooplankton biomass and copepod abundance. Current meters were deployed on moorings near the transect and the data used to model flows and mixing on the NW Shelf and in the Gulf. The majority of reef, pelagic and baitfish larvae (81, 83 and 66% respectively) were collected at only two stations that marked the boundary between stratified waters offshore and well‐mixed water within the Gulf. Most baitfishes (primarily Spratelloides spp.) were captured by traps deployed near the seabed, while reef fishes (mostly pomacentrids, lethrinids and siganids) and pelagic species (mostly scombrids and carangids) were captured in traps deployed near surface. Catch composition varied between summers with 64% of baitfishes collected in the first summer, while the majority of reef and pelagic fishes (81 and 80% respectively) were captured in the second summer. Modelling of circulation showed that the velocity of tidal currents was enhanced by constriction of flow between NW Cape and South Muiron Island and by shallowing of the shelf. Flood‐tide intrusions of water allowed the thermocline to move up the continental shelf, upwelling cool nutrient‐rich water that was then mixed throughout the entire water column at stations in the mouth of the Gulf. This upwelling and mixing resulted in higher chlorophyll a concentrations and copepod abundances either as a result of local in situ growth or advection/aggregation processes, and may account for the great abundances of late‐stage fish larvae in the mouth of the Gulf.

AGAGE Observations of Methyl Bromide and Methyl Chloride at Mace Head, Ireland, and Cape Grim, Tasmania, 1998–2001 - P. G. Simmonds; R. G. Derwent; A. J. Manning; P. J. Fraser; P. B. Krummel; S. O'Doherty; R. G. Prinn; D. M. Cunnold; B. R. Miller; H. J. Wang; D. B. Ryall; L. W. Porter; et al. (Journal of Atmospheric Chemistry, 2004)

Subcutaneous Administration of a Recombinant Vaccinia Virus Vaccine Expressing Multiple Envelopes of HIV-1 - K. S. Slobod; T. D. Lockey; N. Howlett; R. V. Srinivas; S. D. Rencher; P. J. Freiden; P. C. Doherty; J. L. Hurwitz (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Are rare primate taxa specialists or simply less studied? - D. A. Doherty; A. H. Harcourt (Journal of Biogeography, 2004)
Aim Rare species are reported to be specialized. However, rare taxa are usually less studied than are common taxa. If so, the reported specialization might be just a result of paucity of records. We here test for this sampling artefact in primates, a taxon in which rarity has been explained by specialization. Location Tropical Africa, Madagascar, Asia, Americas. Methods We define rare and common species as those with geographical range sizes in the lower and upper quartiles, respectively, for primates in each realm. We conducted two independent searches of published literature to determine if there were significantly fewer studies on a common measure of specialization, diet, for rare vs. common species. We then tested for sampling artefact in reported diet breadth by comparing the number of references needed to obtain it for both rare and common species. Results We found, in both literature searches, significantly fewer studies on diet for rare primates – a mode of zero references for rare species, and one for common. By contrast, no significant difference existed for number of references needed to attain the full reported diet breadth: a median of one reference for both specialized, rare and generalized, common species. Main conclusions Rare species are indeed studied less. Nevertheless, the finding that rare primates are specialists is not necessarily mere sampling artefact.

Low frequency of the "plateau phenomenon" during maximal exercise in elite British athletes - M. Doherty; L. Nobbs; T. D. Noakes (European Journal of Applied Physiology, 2003)

Characterisation of the expression of a novel constitutive maize promoter in transgenic wheat and maize - S. Rasco-Gaunt; D. Liu; C. Li; A. Doherty; K. Hagemann; A. Riley; T. Thompson; C. Brunkan; M. Mitchell; K. Lowe; E. Krebbers; P. Lazzeri; et al. (Plant Cell Reports, 2003)

Fully coupled climate/dynamical vegetation model simulations over Northern Africa during the mid-Holocene - R. Doherty; J. Kutzbach; J. Foley; D. Pollard (Climate Dynamics, 2000)

Hydroxyl Radical Concentrations Estimated from Measurements of Trichloroethylene during the EASE/ACSOE Campaign at Mace Head, Ireland during July 1996 - R. G. Derwent; N. Carslaw; P. G. Simmonds; M. Bassford; S. O'Doherty; D. B. Ryall; M. J. Pilling; A. C. Lewis; J. B. McQuaid (Journal of Atmospheric Chemistry, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Isolation of salmon pancreas disease virus (SPDV) from farmed Atlantic salmon, Salmo salar L., in Scotland - H. M. Rowley; C. E. Doherty; M. F. McLoughlin; M. D. Welsh (Journal of Fish Diseases, 1998)
A toga‐like virus was recently isolated in the present authors' laboratory from Atlantic salmon during an outbreak of PD in Ireland (Nelson, McLoughlin, Rowley, Platten & McCormick 1995). When inoculated into Atlantic salmon post‐smolts, this virus, known as salmon pancreas disease virus (SPDV), caused pathological changes in the pancreas, heart and skeletal muscle which were indistinguishable from those observed in natural outbreaks of PD (McLoughlin, Nelson, Rowley, Cox & Grant 1996). In 1996 a serological survey was carried out to determine the presence and distribution of antibodies to SPDV in Irish, Scottish and Norwegian farm‐reared Atlantic salmon (McLoughlin, Rowley & Doherty 1998). The results of this survey indicated that SPDV is present in the major European salmon‐producing countries. The present paper describes the first isolation of SPDV from farm‐reared, PD‐affected Atlantic salmon in Scotland.